Assessing beliefs about emotion generation and change: The conceptualisation, development, and validation of the Cognitive Mediation Beliefs Questionnaire (CMBQ). (3rd October 2021) - Turner, Martin J.; Wood, Andrew G.; Boatwright, Daniel; Chadha, Nanaki; Jones, Jennifer K.; Bennett, Richard
Abstract: The ability to regulate emotions is important for human function and health. That emotion regulation can be achieved through cognitive change is predicated on the notion of cognitive mediation. However, the extent to which individuals believe that their emotions are cognitively mediated (C–M), or in contrast, that their emotions occur via stimulus-response (S-R), is underexplored, and whether C–M and S-R beliefs shape emotion reactivity is not yet known. Research that addresses these empirical needs could inform emotion regulation interventions such as cognitive behavioural therapies (CBTs). The current paper reports the development and initial validity testing of the cognitive mediation beliefs questionnaire (CMBQ). Five studies report the factor structure, the construct and criterion validity, and the test-retest reliability of the CMBQ. The CMBQ was found to have a correlated two-factor structure (C–M change beliefs, and S-R generation beliefs). Higher C–M change beliefs and lower S-R generation beliefs were related to greater emotion regulation, greater thought control ability, higher positive mental health, and lower emotion reactivity. The CMBQ also demonstrated acceptable test-retest reliability. Initial testing indicates that the CMBQ is a valid and reliable questionnaire for psychometric use in adult populations, including those with a diagnosed mental health condition.